A Randomised Comparative Study Between Usg Guided Alone And Usg Gudied Plus Neurostimulation Technique For Brachial Plexus Block Through Supra-Clavicular Approach For Upper Limb Surgeries - Dr. Kalwani Karankumar Dilipbhai; Dr. Swati Dawalwar; Dr. Yatish Jadhav; Dr. Anand Kamble (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Ultrasound (US) guidance is standard for peripheral nerve blocks, yet the incremental benefit of adding peripheral nerve stimulation (PNS) remains debated. Objective: To compare block-performance time, sensory–motor characteristics, success rate and analgesic profile of (a) US guidance alone and (b) US + PNS for supraclavicular brachial plexus block (SCBPB) in adults. Methods: Sixty ASA I–II patients (18–65 y) scheduled for elective upper-limb surgery were randomised to US (n = 30) or US + PNS (n = 30). After standard preparation, 20 mL 0.5 % bupivacaine was injected. The primary outcome was block-performance time. Secondary outcomes included onset/duration of sensory and motor block, verbal numeric rating scale (VNRS) pain scores, rescue analgesia, haemodynamics and complications. Results: Groups were demographically comparable (Table 1). US alone was faster to perform (9.23 ± 1.79 min vs 11.56 ± 2.17 min; p < 0.0001) but US + PNS yielded quicker motor onset (grade 1: 8.80 ± 2.98 min vs 11.46 ± 1.79 min) and prolonged sensory (566.6 ± 115.8 min vs 475.6 ± 89.8 min) and motor (548.5 ± 120.4 min vs 453.7 ± 83.3 min) duration (p < 0.0001). VNRS pain scores were significantly lower in US + PNS at 6, 8 and 12 h post-block. Success rate was 100 % in both groups; no major complications occurred. Conclusions: Adding PNS modestly lengthens set-up time but delivers faster onset, longer analgesia and lower early postoperative pain without added risk. US + PNS therefore offers clinically meaningful advantages when prolonged peri-operative analgesia is desired.